APPLICATION OF NUMBER HEADS TOGETHER COOPERATIVE LEARNING MODELS TO IMPROVE LEARNING ACTIVITY AND ACHIEVEMENT - Chandra Arisandy; Johanes Sapri (DIADIK, 2019)
The purpose of this study is to apply the Number Heads Together (NHT) learning model to improve student activity and achievement. This research has been carried out by means of classroom action research in Lahat 11 Public Elementary School. This research was conducted in three cycles to find out that the application of the NHT learning model improves student achievement results from the first cycle to the third cycle. This proves that the application of the NHT type of cooperative learning model not only increases student learning activities but also increases the understanding ofthe material and this has the effect of increasing student learning outcomes. PTK taking techniques by observation and tests, while the experimental class only tested the NHT learning model that took grade 5 c. Data analysis was carried out with significant significance using t-test. Based on the analysis of this research data, it was found that there are differences in learning models that use NHT to improve student learning activities and achievement in mathematics learning